If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Oblicz to!
(55/3)*(9-6) = 0
y = -2*x^2-4*x-3;-2;-4;-3
-(((-4)^2-(-3*(-2)*4))/(-2*4))
-(-4/(-2*2))
-2*0^2-(0*4)-3
| -1.8+0.5w=0.6(w+2) | | Log^4(2x+6)=1 | | x^4+3x^3+x^2-17x+19=0 | | 10b-(4b-8)=20 | | 5(2-3x)-17(2x-5)=16 | | 0.6x+0.5y=450 | | (8i)/(3-6i) | | (3/4)^-1 | | 5n-2=3 | | Log(3)(1/3) | | 2log(3)(x)-log(3)(6x)=1 | | y=-8x-6logx | | f(x)=-8x+6lnx | | 3(2x+1)+7(6x-1)=5(12x-7)+23 | | x^2-8x+924=0 | | abs(x^2-64)=0 | | xy-15x+5Y-1575=0 | | 6+2y=4(y-1) | | 2.5x-1.5x=1500 | | (.3x-1.34)=y | | -12=-4523+2y | | x(sec^2x+1)=0 | | 5x+3-5x=15 | | 2(5x-1)=58 | | 3(7+2x)=51 | | 4(2x+8)=56 | | 3(4+2x)=30 | | 3x^0+4y^3= | | 2(4x+4)=32 | | 4[x-4/4x-1] | | s^2+8s+16-81=0 | | 5x+0.25y+0.75z=100 |